PENGGUNAAN SLANG DI LINGKUNGAN SEKOLAH SISWA SMP MAKASSAR MULYA: The Use of Slang in the School Environment of Smp Makassar Mulya Students - Nurul Annisa, Fajrina; Mayong; Nurhusna (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This research aims to (1) describe the form of slang in the school environment of Makassar Mulya Middle School students and (2) describe the influence of the use of slang in the school environment of Makassar Mulya Middle School students on the existence of the Indonesian language. This research is a qualitative descriptive research. using listening and note-taking techniques and equipped with recording and distributing questionnaires. The results of the research show that there are 4 forms of slang used by Makassar Mulya Middle School students, namely: abbreviations, puns, acronyms and new vocabulary. The influence of the use of slang in the school environment of Makassar Mulya Middle School students, namely: related to aspects of creativity, social identity, and adaptation to dynamic cultural changes. Slang has several positive influences, but its excessive or inappropriate use can also have various negative influences on the existence of the Indonesian language, especially related to the decline in the quality of formal language, the potential for misunderstandings, erosion of language norms, and the formation of inappropriate language habits